Long-Term Tillage and Nitrogen Fertilization Effects on Soil Surface Chemistry - A. Obour; J. D. Holman (Kansas Agricultural Experiment Station Research Reports, 2017)
Long-term crop management practices can affect nutrient cycling and availability to crops. This study examined the long-term effects of nitrogen (N) fertilizer application (N rates of 0, 20, 40, and 60 lb N/a) and tillage intensity (conventional tillage (CT), reduced tillage (RT), and no-tillage (NT)) on soil phosphorus (P), micronutrients, and soil acidity in a dryland winter wheat (Triticum aestivumL.)–sorghum (Sorghum bicolorL.)–fallow cropping system. Results showed soil organic matter (SOM), iron (Fe), and zinc (Zn) concentrations were greater under NT compared to CT or RT. Similarly, NT ( 32 ppm) increased P accumulation in the upper 3 in. soil depth compared to CT (21 ppm) or RT (26 ppm). Soil pH at the surface (0 to 3 in.) declined markedly with increasing N fertilizer application rate, ranging from 6.1 with the control to 5.5 when 60 lb N/a was applied. Averaged across N rates, soil pH was lower with NT (5.7) compared to CT (6.3) and RT (6.2) treatments. Iron and manganese (Mn) concentrations increased with increasing N application rates, probably due to the decrease in pH associated with N application.
Keywords: Tillage; nutrient stratification; pH